Exact Solutions and Conservation Laws of the Bogoyavlenskii Equation - İnç, Mustafa; Hashemi, M. S.; Aliyu, A. Isa (Polish Acad Sciences Inst Physics, 2018)
In this paper, the Lie symmetry analysis method is performed for a Bogoyavlenskii equation. The symmetries and exact invariant solutions for the equation are retrieved for the first time. The conservation laws of the Bogoyavlenskii equation are constructed using the conservation laws theorem introduced by Ibragimov.
Keywords: Lie Symmetry; Nonlinearity; Solitons